Gene-Expressing Liposomes as Synthetic Cells for Molecular Communication Studies - Rampioni, Giordano; D'Angelo, Francesca; Leoni, Livia; Stano, Pasquale (Frontiers in Bioengineering and Biotechnology, 2019)
The bottom-up branch of synthetic biology includes – among others – innovative studies that combine cell-free protein synthesis with liposome technology to generate cell-like systems of minimal complexity, often referred to as synthetic cells. The functions of this type of synthetic cell derive from gene expression, hence they can be programmed in a modular, progressive and customizable manner by means of ad hoc designed genetic circuits. This experimental scenario is rapidly expanding and synthetic cell research already counts numerous successes. Here we present a review focused on the exchange of chemical signals between liposome-based synthetic cells (operating by gene expression) and biological cells, as well as between two populations of synthetic cells. The review includes a short presentation of the “molecular communication technologies”, briefly discussing their promises and challenges.